Dynamic microfluidic bioreactor—Hip simulator (DMBH) system for implant toxicity monitoring. Issue 12 (12th October 2021) - Badhe, Ravindra V.; Bijukumar, Divya; Mesquita, Pedro; Cheng, Kai Yuan; Ramachandran, Remya Ampadi; Lin, Yang; Mathew, Mathew T.
Abstract: The generation of degradation products (DPs) like ions and organo‐metallic particles from corroding metallic implants is an important healthcare concern. These DPs generate local and systemic toxicity. The impact on local toxicity is well documented, however, little is known about systemic toxicity. This is mainly due to the limited scope of the current microtiter plate‐based (static) toxicity assay techniques. These methods do not mimic the systemic (dynamic) conditions. In this study, it is hypothesized that DPs incubated with cells in static conditions might provide improper systemic toxicity results, as there is no movement mimicking the blood circulation around cells. This study reports the development of a three‐chambered prototype microfluidic system connected to the operational hip implant simulator to test the cellular response induced by the DPs. This setup is called a dynamic microfluidic bioreactor—hip simulator system. We hypothesize that a dynamic microfluidic system will provide a realistic toxicology response induced by DPs than a static cell culture plate. To prove the hypothesis, Neuro2a (N2a) cells were used as representative cells to study systemic neurotoxicity by the implant DPs. The microfluidic bioreactor system was validated by comparing the cell toxicity against the traditional static system and using COMSOL modeling for media flow with DPs. The hip implant simulator used in this study was a state‐of‐the‐art sliding hip simulator developed in our lab. The results suggested that static toxicity was significantly more compared to dynamic microfluidic‐based toxicity. The newly developed DMBH system tested for in situ systemic toxicity on N2a cells and demonstrated very minimum toxicity level (5.23%) compared to static systems (31.16%). Thus, the new DMBH system is an efficient tool for in situ implant metal systemic toxicity testing. Abstract : In‐vitro systemic toxicity analysis of the products generated during the functioning of metallic implants has always been a challenge. Many implant simulators were developed but the toxicity assays preformed for the generated degradation products are still being tested using traditional static (microtiter) systems. In attempt to develop efficient In‐vitro systemic toxicity testing system 'Dynamic Microfluidic Bioreactor Hip simulator' (DMBH) system is developed. Studies clearly showed that DMBH system provide realistic systemic toxicity analysis for hip implant simulator generated degradation products.